Legal Dımensıons Of Lendıng By Dıgıtal Banks In Indonesıa - Jonker Sihombing (Cita Konsultindo Research Center, 2024)
The existence of digital banks today is a real need amidst the development of information technology and banking services which must be able to cover all levels of society. These banking services mainly consist of credit granting to the public. This research aims to analyze the extent to which the know-your-customer principle and the prudential banking principle are implemented for digital banks in credit granting. This research is normative juridical, using secondary data comprising primary legal materials in the form of statutory regulations, and secondary legal materials in the form of books, literature and academic journals. The research results show that know-your-customer principle and prudential banking principle that apply to commercial banks also apply to digital banks. However, there are no specific regulations for digital banks that regulate those, especially for lending activities that are full of risk. The research results also show that there are disparities in the application of know-your-customer and prudential banking principles by digital banks. It is recommended for the Financial Service Authority (Otoritas Jasa Keuangan/OJK) to regulate and supervise digital bank activities more intensively, especially in credit granting.